Crise em fragmentos: subjetividade e saúde mental no cotidiano dos caps em Vitória/ES - Castro, Karla Maria Duarte (2019)
The Brazilian Psychiatric Reform and the Antimanicomial Struggle Movement, in their ethical-political principles, operate vastly in the care/assistance/human rights in severe psychological distress, but today we are under the attacks and risks of setbacks in Brazilian mental health policies. This movements are important for the creation of social networks, the production of local and intersectoral policies and the creation of territorial substitute service networks, as well as for overcoming the asylum model and for creating a psychosocial way of caring. Thus, one of the greatest achievements in Brazil was the creation of Psychosocial Care Centers (NAPS / CAPS), in the Ordinance category nº 3.088/MS of December 23, 2011. Think how the CAPS in Vitória-ES, which take care of people in severe psychic distress and were the result of social claims for strategies of mental health care replacing the biomedical and asylum hegemonic model, has welcomed the crisis process when it happens in daily life, was the guide of this research. By participating in various spaces of care in the equipment, it was possible to follow how attention to the crisis unfolds in the daily routine of services, how affects are mobilized to produce care that does not fragment subject/life. It has been witnessed that everyday issues such as the use of the toilet and the breakfast time, when discussed in assemblies produce beyond therapeutic effects, a democratic exercise which becomes a place of agreement that reverberates in users' lives, increasing their autonomy.